2014
DOI: 10.1371/journal.pone.0098762
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Cell Behaviors through Cell Cycle Progression via Automated Cell Tracking

Abstract: Cell behaviors are reflections of intracellular tension dynamics and play important roles in many cellular processes. In this study, temporal variations in cell geometry and cell motion through cell cycle progression were quantitatively characterized via automated cell tracking for MCF-10A non-transformed breast cells, MCF-7 non-invasive breast cancer cells, and MDA-MB-231 highly metastatic breast cancer cells. A new cell segmentation method, which combines the threshold method and our modified edge based acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
(40 reference statements)
3
17
0
Order By: Relevance
“…We tracked this GFP-positive DG motion (Fig 2E and 2F; Suppl. Movies SM8 and SM9) and fitted the recorded xy positions over time using mathematical models of “directed” or “diffusive” motion (see M&M) [32]. We confirmed that the DG trajectory 2 is consistent with a “directed” motion (fitted curve, Fig 2F), characteristic of a vesicle moving along cytoskeleton tracks, in contrast to the trajectories 1 and 3, consistent with “confined diffusive” motions [32].…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…We tracked this GFP-positive DG motion (Fig 2E and 2F; Suppl. Movies SM8 and SM9) and fitted the recorded xy positions over time using mathematical models of “directed” or “diffusive” motion (see M&M) [32]. We confirmed that the DG trajectory 2 is consistent with a “directed” motion (fitted curve, Fig 2F), characteristic of a vesicle moving along cytoskeleton tracks, in contrast to the trajectories 1 and 3, consistent with “confined diffusive” motions [32].…”
Section: Resultssupporting
confidence: 64%
“…Movies SM8 and SM9) and fitted the recorded xy positions over time using mathematical models of “directed” or “diffusive” motion (see M&M) [32]. We confirmed that the DG trajectory 2 is consistent with a “directed” motion (fitted curve, Fig 2F), characteristic of a vesicle moving along cytoskeleton tracks, in contrast to the trajectories 1 and 3, consistent with “confined diffusive” motions [32]. This result, together with the inhibition of Rab11A-positive vesicle (Fig 1D) and DG [31] movements upon CD treatment, strongly suggests that Rab11A promotes DG transport by mediating DG tethering along actin filaments, at least at the parasite cortex.…”
Section: Resultsmentioning
confidence: 99%
“…MDA‐MB‐231 cells showed the fastest movement followed by MCF‐7 cells and the slowest cells were MCF‐10A cells on average (Figure S6, Supporting Information). The speed of MDA‐MB‐231 cells was one order of magnitude higher than the published average speed of mobile MDA‐MB‐231 cells in 3D Matrigel, and the speed of all three cell lines was in a similar range compared to the instantaneous migration speed in 2D on plastic observed by Wang et al Thus, the movement in the 2.5D glycocalyx resembles more that in 2D rather than that in 3D. In addition, we calculated the mean migration velocities according to the different interaction modes and found that cells penetrating the glycocalyx were the slowest (25 µm h −1 ), followed by adhered cells (38 µm h −1 ), and cells close to the glycocalyx were the fastest (46 µm h −1 ).…”
Section: Resultssupporting
confidence: 47%
“…A slow acquisition speed presents an issue since cells may have the time to change their morphology over the course of the multi‐images acquisition, thus shifting the spatial position of the birefringent components between each frame. Notably, the rate of membrane protrusion and the speed at which a cell can migrate can be as high as 10 μm min −1 . Any slight frame‐to‐frame shift can introduce artifacts from the computational step that provides false retardance signals.…”
Section: Discussionmentioning
confidence: 99%